Good Cooperatives’ Governance and Performance in Banyumas Region - Budiyah, Feriyani; Suyono, Eko (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
This study aims to analyze the influence of good cooperative governance (i.e., transparency, accountability, responsibility, independence, and fairness) on cooperative performance. By using a purposive sampling method this study ended-up with 32 cooperatives in Banyumas as samples with the questionnaires were distributed during August 7-13, 2015. The findings from OLS regression show that all governance variables (i.e., transparency, accountability, responsibility, independence, and fairness) influence positively on cooperative performance. Therefore, with its limitation such as a small number of samples this study contributes to the body of knowledge by providing empirical evidence on how governance variable influences positively for cooperative performance in the lack of study on the issues of good governance for cooperatives.